2017
DOI: 10.1075/lab.15046.dew
|View full text |Cite
|
Sign up to set email alerts
|

Glimpses of semantic restructuring of English emotion-laden words of American English L1 users residing outside the USA

Abstract: The present exploratory study focuses on the effect of living outside the USA on the understanding of the meaning, the perceived offensiveness and the self-reported frequency of use of four English emotion-laden words of British origin and four English emotion-laden words of American origin among 556 first (L1) language users of American English. Statistical analyses revealed that the scores of the Americans living in the UK or in non-English-speaking countries differed significantly from those of compatriots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Besides, the liberating effect of the emotion-laden word "bloody" in humour is in line with Dewaele's (2013) finding that decreased emotionality of emotion-laden words has helped LX users overcome cultural restrictions. The findings in this study showed that this liberating effect also exists among L1 users of different variants, or bi-dialectal or bi-varietal monolinguals (Dewaele, 2015(Dewaele, , 2018b. Lastly, the American English L1 users had not yet become entirely bicultural, as they failed to perceive or appreciate the class-related humour that is a constant source of British humour (Fox, 2004).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Besides, the liberating effect of the emotion-laden word "bloody" in humour is in line with Dewaele's (2013) finding that decreased emotionality of emotion-laden words has helped LX users overcome cultural restrictions. The findings in this study showed that this liberating effect also exists among L1 users of different variants, or bi-dialectal or bi-varietal monolinguals (Dewaele, 2015(Dewaele, , 2018b. Lastly, the American English L1 users had not yet become entirely bicultural, as they failed to perceive or appreciate the class-related humour that is a constant source of British humour (Fox, 2004).…”
Section: Discussionmentioning
confidence: 88%
“…Dewaele (2015) found significant differences in the semantic and conceptual representations of negative emotion-laden English words of American and British origin among British and American English L1 users 1 . In a follow-up study focusing on the American English L1 users, Dewaele (2018b) found that the semantic and conceptual representations of the words of British origin ("daft", "bollocks", "bugger", "wanker") had shifted significantly in the group of Americans who had lived outside the US. No change was observed in the representations of the words of American origin.…”
Section: Introductionmentioning
confidence: 99%
“…(3) How frequently do you use it?". We have argued that the feedback on the three questions offers a glimpse of semantic and -possibly-also of conceptual representations (Dewaele 2017a). Participants' responses about the meaning of a word might give a subjective general indication, but it is impossible to conclude that those who reported complete understanding of the word actually had an accurate representation.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…The differences in the semantic representations of emotion words were also studied amongst three different types of English L1 users (Dewaele, 2018b). The three groups of Americans living in the United States, in the United Kingdom, and in non-Englishspeaking countries participated in an online survey about the perceived offensiveness of four offensive words of American origin and another four of British origin.…”
Section: The Verbal Channel: Emotion Wordsmentioning
confidence: 99%